An investigation into the use of information communication technology (ICT) in the teaching of Geography at ö"level in Mhondoro Ngezi District schools - Muwani, Adonia (Midlands State University, 2020)
The purpose of this study was to investigate into the use of Information Communication technology in the teaching of Geography at ‘O’ level in Mhondoro Ngezi District Secondary Schools. Descriptive survey design which utilized mixed approach method was used. Questionnaires were administered to thirteen teachers teaching Geography at selected schools. School heads of three schools were interviewed. Purposive sampling technique was used to select teachers for study. The findings revealed that teachers lack knowledge and skills in the use of ICT tools in Geography. They also have no access to ICT tools. In addition there is lack of ICT policy in schools and also no professional development for teachers pertaining the topic. Some schools are not electrified hence execution of ICT is hindered in Geography lessons. There is also scarcity of infrastructure such as computer laboratories and computers. The study recommends that school heads must familiarize themselves with the national ICT policy in a bid to implement it in schools. The government must increase in service training programmes on use of ICT tools in geography lessons. Conclusions from the study indicated that teachers are still having problems in using technological tools like computers, projectors , internet, email and other softwares like global positioning softwares commonly in use in other countries like Australia , Malaysia, China and South Africa.